Epidemiologic update on the dengue situation in the Western Pacific Region, 2011 - Tamano Matsui; Hwi Kwang Han; Zoe Rebecca Edelstein; Yuzo Arima (World Health Organization Regional Office for the Western Pacific, 2013)
Dengue is an emerging vectorborne infectious disease that is a major public health concern in Asia and the Pacific. Official dengue surveillance data for 2011 provided by ministries of health were summarized as part of routine activities of the World Health Organization Regional Office for the Western Pacific. Based on officially reported surveillance data, dengue continued to show sustained activity in the Western Pacific Region. In 2011, Member States reported a total of 244 855 cases of which 839 died. More than 1000 cases were reported each from Cambodia, the Federated States of Micronesia, the Lao People's Democratic Republic, Malaysia, the Philippines, the Marshall Islands, Singapore and Viet Nam. Cambodia, the Federated States of Micronesia and the Marshall Islands reported more cases relative to 2010. There continues to be great variability among the dengue-endemic countries and areas in the Region in the number of cases and serotype distribution. The continued high notification rate and complex dengue epidemiology in the Region highlight the need for information-sharing on a routine and timely basis.